Enantioselective Diels–Alder reaction in the confined space of homochiral metal–organic frameworks. Issue 112 (23rd November 2016) - Tanaka, Koichi; Nagase, Shohei; Anami, Taku; Wierzbicki, Michał; Urbanczyk-Lipkowska, Zofia
Abstract : A novel homochiral porous MOF synthesized using ( R )-2, 2′-dihydroxy-1, 1′-binaphthyl-4, 4′-dibenzoic acid was shown to be an effective heterogeneous catalyst for asymmetric Diels–Alder reaction between isoprene and N -ethyl maleimide. Abstract : A novel homochiral porous metal–organic framework (MOF) has been synthesized using ( R )-2, 2′-dihydroxy-1, 1′-binaphthyl-4, 4′-dibenzoic acid as the chiral ligand. This MOF acts as an effective heterogeneous catalyst for the enantioselective Diels–Alder reaction between isoprene and N -ethyl maleimide.